2003
DOI: 10.4049/jimmunol.171.3.1164
|View full text |Cite
|
Sign up to set email alerts
|

IL-18 Binding Protein Protects Against Contact Hypersensitivity

Abstract: Allergic contact dermatitis, the clinical manifestation of contact hypersensitivity, is one of the most common disorders of the skin. It is elicited upon multiple cutaneous re-exposure of sensitized individuals to the sensitizing agent. In this study, we demonstrate that using IL-18 binding protein (IL-18BP) to neutralize IL-18 significantly reduced clinical symptoms in a murine model of contact hypersensitivity. Furthermore, IL-18BP alleviated the relapses during established disease, as indicated by significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 39 publications
0
34
0
2
Order By: Relevance
“…The disease-limiting action of AdIL-18bp was a robust finding that was reproduced in EAE induced by two different encephalitogens in two strains of mice, and was observed in two separate animal facilities. IL-18bp has beneficial effects in a variety of model system of inflammatory disease, including contact hypersensitivity (20), diabetes (21), and models of inflammation-induced liver disease (18,19). In the CNS, IL-18bp was shown to have a beneficial effect on recovery from closed head trauma (22), and MBPspecific Th2 cell lines engineered to express IL-18bp had a beneficial effect on EAE (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease-limiting action of AdIL-18bp was a robust finding that was reproduced in EAE induced by two different encephalitogens in two strains of mice, and was observed in two separate animal facilities. IL-18bp has beneficial effects in a variety of model system of inflammatory disease, including contact hypersensitivity (20), diabetes (21), and models of inflammation-induced liver disease (18,19). In the CNS, IL-18bp was shown to have a beneficial effect on recovery from closed head trauma (22), and MBPspecific Th2 cell lines engineered to express IL-18bp had a beneficial effect on EAE (44).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that IL-18bp can inhibit IL-18R signaling via an IL-18-independent interaction with IL-18Rb subunit (17). Several studies have demonstrated that administration of exogenous IL-18bp can have a therapeutic effect in a variety of inflammatory diseases (18)(19)(20)(21), and IL-18bp improved recovery in a model of closed head trauma (22), although there is a paucity of studies on the role of IL-18bp in the CNS.…”
mentioning
confidence: 99%
“…Macrophage accumulation in association with increased IL-18 expression has been described in a number of other inflammatory and immune-mediated processes, including biliary atresia, 39 contact hypersensitivity, 40 and lupus-like autoimmune syndrome. 27,28 Of particular interest, in the setting of rheumatoid arthritis, increased production of IL-18 associated with these inflammatory processes is principally from macrophages.…”
Section: Il-18mentioning
confidence: 99%
“…Orthopoxvirus IL-18BP contributes to virulence by downmodulating IL-18-mediated immune responses (5,9). The mechanism by which IL-18BP inactivates hIL-18 is unclear, but its potent ability to inhibit hIL-18 has prompted an interest in developing IL-18BP as therapeutics (10,11) because aberrant expression of IL-18 is associated with severe inflammatory conditions, such as some autoimmune diseases. Recombinant human IL-18BP has been shown to be effective at treating inflammatory skin diseases and LPS-induced liver injury (10,11).…”
mentioning
confidence: 99%